2018
DOI: 10.3389/fphar.2018.01175
|View full text |Cite
|
Sign up to set email alerts
|

Human Adipose Tissue-Derived Mesenchymal Stem Cells Attenuate Atopic Dermatitis by Regulating the Expression of MIP-2, miR-122a-SOCS1 Axis, and Th1/Th2 Responses

Abstract: The objective of this study was to investigate the effect of human adipose tissue-derived mesenchymal stem cells (AdMSCs) on atopic dermatitis (AD) in the BALB/c mouse model. The AdMSCs attenuated clinical symptoms associated with AD, decreased numbers of degranulated mast cells (MCs), IgE level, amount of histamine released, and prostaglandin E2 level. Atopic dermatitis increased the expression levels of cytokines/chemokines, such as interleukin-5 (IL-5), macrophage inflammatory protein-1ß (MIP-1ß), MIP-2, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 57 publications
1
36
0
Order By: Relevance
“…AD shares common molecular features with anaphylaxis ( Kim et al., 2018 ). We examined the effect of HHT on AD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AD shares common molecular features with anaphylaxis ( Kim et al., 2018 ). We examined the effect of HHT on AD.…”
Section: Resultsmentioning
confidence: 99%
“…SOCS1, decreased by TGFβ, mediates in vitro and in vivo allergic inflammation and binds to FcϵRI (Noh et al., 2017). SOCS1 regulates AD by forming a negative feedback loop with miR-122a-5p ( Kim et al., 2018 ). It is reasonable that HHT may increase expression level of TGFβ and miR-122a-5p.…”
Section: Discussionmentioning
confidence: 99%
“…These reports suggest that PSA mediated by IgE is closely associated with suppression of functions of FOXP3 + Tregs. In atopic dermatitis, the expression of FoxP3, a marker of Treg cells, is decreased [60]. This suggests that anaphylaxis and atopic dermatitis might share molecular features.…”
Section: Effector Cells Effector Molecules and Cellular Interactmentioning
confidence: 99%
“…It also shows angiogenic potential [15] (Figure 2B). We have shown that atopic dermatitis, PCA and PSA display common molecular features such as activation of FcεRI signaling, increased secretion of Th2 cytokines and increased amount of histamine released [60]. Thus, MCP1 might mediate atopic dermatitis and passive anaphylaxis.…”
Section: Hdac3 Mediates Anaphylaxismentioning
confidence: 99%
See 1 more Smart Citation